Barriers to urban management in the viability of cities, Case study: Semnan city - abbas Babaei; zeinab korke abadi; saeid kamyabi (تحقیقات کاربردی علوم جغرافیایی)
Promoting urban livability and realizing a livable city are closely linked to how the urban management apparatus and institutions and organizations active in urban affairs function. Municipalities, as the most important coordinating body in urban affairs, have played a decisive role in solving urban problems and are responsible for the social and physical development of cities. In fact, municipalities have the main task of serving the citizens and play the most important role in improving the quality of life of citizens. The purpose of this study is to evaluate the viability level of Semnan city and analyze the problems of Semnan city from the perspective of different groups (officials-elites). The research method is descriptive-analytical and the research tool is a questionnaire. The validity and reliability of this research has been confirmed by the previous similar research and the opinions of the supervisors and advisors of the dissertation, the validity of the research tools. The internal validity of the instrument (questionnaire) is also shown through the Cronbach's alpha with a value of 0.84 for the questionnaires. The results showed that among the total biomarker indicators of Semnan city, from the point of view of elites and officials (with an average of 2.76), it was evaluated at a low level. Also, based on prioritization with ANP technique, "Improving Institutional-Organizational Capacity in Optimal Urban Management (R7)" with the highest score (07/357: 357) was identified as the best solution and in fact the main solution to deal with urban issues in Semnan. Also, the strategy of "integrated management between urban organizations to coordinate in the management of urban affairs (R6)" with (06/3366) was selected as the second solution.